Diagnostic performance of procalcitonin, presepsin, and C‐reactive protein in patients with hematological malignancies. Issue 6 (30th January 2017) - Ebihara, Yasuhiro; Kobayashi, Kiyoko; Ishida, Akaru; Maeda, Tomoya; Takahashi, Naoki; Taji, Yoshitada; Asou, Norio; Ikebuchi, Kenji
Abstract : Introduction: Infections represent a major complication of hematological malignancies. C‐reactive protein (CRP) and procalcitonin (PCT) have been used as diagnostic biomarkers of infections, but do not produce definitive findings. Recently, a new biomarker, presepsin, has been used as a diagnostic tool for detecting infections in the fields of emergency and neonatal medicine. However, the usefulness of presepsin for identifying infections in patients with hematological malignancies, including those who develop febrile neutropenia, remains unclear. Methods: In this study, we retrospectively analyzed the utility of PCT, presepsin, and CRP as biomarkers of infections during 49 febrile episodes that occurred in 28 patients with hematological malignancies. Results: The levels of PCT, but not those of CRP or presepsin, were significantly higher in the infection group than in the uninfected group ( P <.03), indicating that PCT might be a more sensitive biomarker of infections. No differences in presepsin levels were detected between the patients with and without neutropenia, or between the infected and uninfected patients with neutropenia, indicating that presepsin might have less diagnostic value in patients with neutropenia. Conclusions: We conclude that PCT might provide additional information and could be used in combination with other biomarkers to detect infections in patients with hematological malignancies.